2007
DOI: 10.1089/jmf.2006.255
|View full text |Cite
|
Sign up to set email alerts
|

A Medicinal Extract ofScutellaria baicalensisandAcacia catechuActs as a Dual Inhibitor of Cyclooxygenase and 5-Lipoxygenase to Reduce Inflammation

Abstract: A mixed extract containing two naturally occurring flavonoids, baicalin from Scutellaria baicalensis and catechin from Acacia catechu, was tested for cyclooxygenase (COX) and 5-lipoxygenase (5-LOX) inhibition via enzyme, cellular, and in vivo models. The 50% inhibitory concentration for inhibition of both ovine COX-1 and COX-2 peroxidase enzyme activities was 15 microg/mL, while the mixed extract showed a value for potato 5-LOX enzyme activity of 25 microg/mL. Prostaglandin E2 generation was inhibited by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
142
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 46 publications
8
142
0
1
Order By: Relevance
“…Unlike the typical 5-LOX inhibitor zileuton, baicalin did not inhibit baseline 5-LOX enzymatic activity but did inhibit the activity after OGD/recovery. Consistently, it has been reported that baicalin shows no inhibition of isolated potato 5-LOX [28] and non-stimulated rat cortical neurons [13] . Moreover, baicalin showed anti-oxidative activity because it reduced ROS production.…”
Section: Wwwchinapharcom LI Ct Et Alsupporting
confidence: 81%
“…Unlike the typical 5-LOX inhibitor zileuton, baicalin did not inhibit baseline 5-LOX enzymatic activity but did inhibit the activity after OGD/recovery. Consistently, it has been reported that baicalin shows no inhibition of isolated potato 5-LOX [28] and non-stimulated rat cortical neurons [13] . Moreover, baicalin showed anti-oxidative activity because it reduced ROS production.…”
Section: Wwwchinapharcom LI Ct Et Alsupporting
confidence: 81%
“…Gastric antiulcer activity has been demonstrated for aqueous extract of heartwood of the plant (Rajendra et al, 2011). Other activities reported for extract of whole plant are anti-pyretic, anti-diarrhoeal, hypotensive, hepatoprotective, anti-mycotic and anti-inflammatory activities (Sham et al, 1984;Ray and Thokchom, 2006;Burnett et al, 2007;Nagaraja et al, 2008). Seeds reportedly showed hypoglycemic activity in normal albino rats (Singh et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Cinnamomum cassia (Family-Lauraceae) bark is attributed with numerous medicinal uses such as diaphoretic, antipyretic and analgesic. It is used as a carminative, cardiac stimulant, antioxidant, refrigerant and diuretic.…”
Section: Introductionmentioning
confidence: 99%